Building Personality in Children’s Stories - Saleh, Mohsen A.; Ibrahim, Aram Y. (Humanities Journal of University of Zakho, 2018)
A character structure is one of the important elements in the building process of literary text body, Specialy in narration text. Because the characters are doing, showing and presenting the actions, they creating a plot in the narration leading the plot to the complex then at the end finding the right solution for the plot. There for the character should be so prepared for the child age and be suitable for the psychological dimension of child.This study is an attempt to show theoretically and practically the character kind and the role of them in children stories.